role of telehealth services in the treatment of rare disease: analysis of 1 year of work on the example of anal cancer - S. S. Gordeev; M. Yu. Fedyanin; E. V. Glazkova; V. A. Amosova; A. V. Petrovskiy (Тазовая хирургия и онкология, 2020)
Objective: to assess the potential need for telehealth consultations in regions for the treatment of patients diagnosed with anal cancer and to analyze the most common treatment errors. Materials and methods. We analyzed telehealth consultations provided for 3 Federal districts between April 2019 and April 2020. The following parameters were evaluated: the ratio between the predicted need for telehealth consultations and the real number of requests, the number of medical errors in patients who had already undergone first and / or subsequent treatment stages (according to relevant clinical guidelines). Results. Fifteen telehealth consultations were provided during this year: 13 of them (86.7 %) for disease progression or complications and 2  of them (13.3 %) to determine the initial treatment strategy. Treatment errors were registered in 11 out of 13 cases (84.6 %). The predicted need based on the population size was 565 consultations per year; the predicted need based on the real number of patients visited cancer clinics was 81 consultations. Conclusions. We found many significant errors in treatment regimens of patients with squamous cell anal carcinoma. Wider use of telehealth consultations with Federal centers will ensure the correct choice of the initial treatment strategy.